Effects of canagliflozin on body composition and hepatic fat content in type 2 diabetes patients with non‐alcoholic fatty liver disease. Issue 4 (4th January 2019) - Inoue, Mitsuko; Hayashi, Akinori; Taguchi, Tomomi; Arai, Riina; Sasaki, Sayaka; Takano, Koji; Inoue, Yusuke; Shichiri, Masayoshi
Abstract: Aims/Introduction: Non‐alcoholic fatty liver disease is frequently associated with type 2 diabetes, and constitutes an important risk factor for the development of hepatic fibrosis and hepatocellular carcinoma. Because there remains no effective drug therapy for non‐alcoholic fatty liver disease associated with type 2 diabetes, we evaluated the efficacy of sodium–glucose cotransporter 2 inhibitor. Methods and Materials: In the present pilot, prospective, non‐randomized, open‐label, single‐arm study, we evaluated the effect of 100 mg canagliflozin administered once daily for 12 months on serological markers, body composition measured by bioelectrical impedance analysis method and hepatic fat fraction measured by magnetic resonance imaging in type 2 diabetes patients with non‐alcoholic fatty liver disease. Results: Canagliflozin significantly reduced body and fat mass, and induced a slight decrease in lean body or muscle mass that did not reach significance at 6 and 12 months. Reductions in fat mass in each body segment (trunk, arms and legs) were evident, whereas those in lean body mass were not. The hepatic fat fraction was reduced from a baseline of 17.6 ± 7.5% to 12.0 ± 4.6% after 6 months and 12.1 ± 6.1% after 12 months ( P  <   0.0005 and P  <   0.005), whereas serum liver enzymes and type IV collagen concentrations improved. From a mean baseline hemoglobin A1c of 8.7 ± 1.4%, canagliflozin significantly reduced hemoglobin A1c after 6 and 12 months to 7.3 ± 0.6% and 7.7 ± 0.7% ( P  <   0.0005 and P  <   0.01). Conclusions: Canagliflozin reduced body mass, fat mass and hepatic fat content without significantly reducing muscle mass. Abstract : We investigated whether sodium–glucose cotransporter 2 inhibitor, canagliflozin, had an effect on non‐alcoholic fatty liver disease in 20 patients with type 2 diabetes with non‐alcoholic fatty liver disease using the most accurate magnetic resonance imaging method. Our study showed that sodium–glucose cotransporter 2 inhibitor significantly reduced bodyweight and fat mass, and significantly increased body water content without changing lean body mass and muscle mass in their body compositions, and significantly reduced the hepatic fat fraction by magnetic resonance imaging at 6 and 12 months. Sodium–glucose cotransporter 2 inhibitor provides a long‐term effective therapeutic option for type 2 diabetes patients with non‐alcoholic fatty liver disease.